Efisiensi reproduksi sapi perah PFH pada berbagai umur di CV. Milkindo Berka Abadi Desa Tegalsari Kecamatan Kepanjen Kabupaten Malang - M. Zainudin; M. Nur Ihsan; Suyadi Suyadi (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2014)
The purpose of this experiment was to investigate the effect of different age of Holstein Friesian Cross Breed dairy cows on reproductive efficiency at CV. Milkindo Berka Abadi, Tegalsari Village, Kepanjen Sub District, Malang Regency. The materials of the research used 82 heads of dairy cows which had at least two times of parturition. Data used reproductive data which were collected from Artificial Insemination practices at CV. Milkindo Berka Abadi. Descriptive analysis was used to determine average and deviation standard of Service per Conception (S/C), Days Open (DO) and Calving Interval (CI). Data were analyzed using Multiplet-test. The age of animal influenced significantly (P<0.05) the reproductive parameters e.g. S/C (2.6±1.2 times, 3.6±1.8 times, 4.2±2.8 times and 2.9±2.6 times), DO (184.4±97.2 days, 260.6±159.6 days, 396.9±296.2 days and 263.1±125.2 days) and CI (460.9±97.2 days, 538.8±160 days, 674±296.1 days and 539.7±124.6 days) for the age of 3, 4, 5 and 6 years respectively. It was concluded that the young cows at CV. Milkindo Berka Abadi had more efficient reproductive performance than those for older cows. Keywords : Days Open, Service per Conception, Calving Interval